Marketing communication trends during war in Ukraine - Ruskykh, Stefaniia; Bahles, Michael; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis examines changes in marketing communication trends in Ukraine during wartime, focusing on the adaptation and implementation of new strategies that differ from traditional marketing approaches. The study highlights the shift towards emotional marketing, driven by the need to resonate more deeply with consumers in a time of crisis. Using a mixed-method approach, including case studies, qualitative data collection, and quantitative analysis, the research reveals how wartime conditions have transformed marketing practices in Ukraine since February 24, 2022. The results show the use of emotional storytelling, real-time updates and interactions, integration of donations with financial tools like Banka and Boyovi, and the use of humor, memes, and national symbols in communication strategies. This research provides valuable insights and recommendations for international companies planning to enter the Ukrainian market during wartime.
Vedoucí práce: Michael Bahles
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses